2009
DOI: 10.1007/s00586-009-1047-0
|View full text |Cite
|
Sign up to set email alerts
|

Total disc replacement compared to lumbar fusion: a randomised controlled trial with 2-year follow-up

Abstract: The study design includes a prospective, randomised controlled study comparing total disc replacement (TDR) with posterior fusion. The main objective of this study is to compare TDR with lumbar spinal fusion, in terms of clinical outcome, in patients referred to a spine clinic for surgical evaluation. Fusion is effective for treating chronic low back pain (LBP), but has drawbacks, such as stiffness and possibly adjacent level degradation. Motion-preserving options have emerged, of which TDR is frequently used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 30 publications
7
138
0
7
Order By: Relevance
“…These reports were based upon five independent continuous clinical randomized control trials, reporting for different follow-up periods or containing separated results. Nine reports from the five RCTs with the relevant information are eventually included involving 837 patients [2,3,9,18,20,34,36,41,48].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports were based upon five independent continuous clinical randomized control trials, reporting for different follow-up periods or containing separated results. Nine reports from the five RCTs with the relevant information are eventually included involving 837 patients [2,3,9,18,20,34,36,41,48].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In three studies, the ProDisc-L (Synthes Spine, West Chester, PA) [9,48] and FlexiCore (Stryker Spine, Allendale, NJ) [41] artificial disc were employed compared with circumferential fusion. Berg et al [2] performed artificial disc replacement with one of three following devices: CHARITÉ , ProDisc-L, or Maverick (Medtronic, Memphis, TE, USA) compared with the posterolateral fusion (PLF) with autologous bone graft or posterior interbody fusion (PLIF) with two carbon fiber cages. The clinical outcomes, surgical data, and complications were analyzed in 2-or 5-year follow-up period.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial with two-year follow-up, Fritzell et al [13] have evaluated the cost-effectiveness of disc prosthesis versus lumbar fusion. This paper is a high-quality economic evaluation, using the clinical data reported in a previous study by Berg et al [4]. The purpose of the present study was (1) to compare the costs associated with disc prosthesis with those of a lumbar fusion, and (2) to compare the costeffectiveness of the two procedures using the EQ-5D.…”
Section: Health Technology Assessmentmentioning
confidence: 99%
“…Several randomized [7][8][9][10][11][12] controlled trials have been carried out to compare TDR with lumbar fusion techniques and found no clinically relevant differences in pain or physical function, thus demonstrating that TDR produces at least equivalent clinical results compared with lumbar fusion. Prospective cohort studies of TDR also showed a significant reduction of pain intensity and improvement of functional impairment over short-to midterm follow-up [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%